DISEASE REJUVENATION AS A PEDAGOGICAL VALEOLOGICAL FUNDAMENTAL PROBLEM (Education in the 21st Century, 2024)
Human health is a process of development of mental and physiological functions, maintenance of high working capacity and social activity, but at present, disease rejuvenation is a complex task from both a medical and pedagogical valeological point of view. And the further civilization develops, the more “younger” diseases become. Atherosclerosis, hypertension, myocardial infarction, tumors, diabetes, leukemia and other diseases are diseases acquired by a person at a young age in the conditions of modern civilization, which are directly related to an unhealthy lifestyle. Unhealthy diet, insufficient physical activity (hypodynamics), various kinds of abuse, bad habits, early sexual relations are some of the modern valeological problems that require an integrated approach to prevent negative consequences.The goal of the study is to discuss the rejuvenation of diseases from a pedagogical valeological point of view based on our studies that reveal the cause-and-effect relationship between the rejuvenation of diseases and a decrease in students’ academic performance. The study was conducted among 28 university tutors, 40 school teachers, 50 schoolchildren, 100 students.